Contact metamorphism associated to the Penamacor - Monsanto granitic intrusion (Central Portugal): geochemical, isotopic and mineralogical features - Costa, Isabel Ribeiro da (2018)
Contact metamorphism related to Variscan and late-Variscan granitic plutons in the Iberian Peninsula is superimposed on medium-grade regional metamorphism, making it often difficult to evaluate per se the thermal effects due to those intrusions and explaining the paucity of scientific literature on the subject. An exhaustive set of geochemical, isotopic and mineralogical data on the contact-zone metasediments hosting the Penamacor-Monsanto granite (Central Iberian Zone, Portugal) provides a significant contribution to the characterization of low- to intermediate-grade contact metamorphism in geological contexts formerly affected by regional metamorphism. The metasediments hosting the Penamacor-Monsanto pluton belong to the extensive detrital sequence of the ante-Ordovician Schist-Greywacke Complex. Bulk geochemistry, oxygen isotope data and crystal-chemistry of key minerals from those contact-zone and neighbouring metasediments have made it possible to infer metamorphic conditions on the contact zone of this granitic intrusion, and to distinguish them from late boron-metasomatism at the exocontact. Mineral paragenesis (muscovite + biotite + chlorite  quartz  plagioclase  cordierite, in spotted-schists; biotite + chlorite  quartz  plagioclase ( cordierite), in hornfelses) and the composition of these coexisting mineral phases indicate that most of the contact rocks reached the biotite zone (or even the cordierite zone, in some cases), equivalent to upper greenschist – lower amphibolite metamorphic grade. The relatively narrow range of O-isotope temperatures estimated for the crystallization of the marginal granites (550-625ºC) explains the absence of significant effects of thermal flow anisotropy on the contact-zone rocks. Besides, textural, paragenetic, mineralogical, isotopic and geochemical nuances observed in hornfelses and spotted-schists seem mainly related to the local host-rock heterogeneities, rather than to thermal effects. The relatively low temperatures estimated for granitoid emplacement and their restricted isotopic and mineralogical impacts on the metasedimentary host-rocks account for the narrow metamorphic aureole associated with the Penamacor-Monsanto pluton, and suggest this massif may correspond to the outcropping tip of a larger granitic intrusion at depth.